A Closer Look at Delayed Primary Cleft Surgery and Unrepaired Cleft Lip and/or Palate in 5 UK Cleft Centers. (June 2022) - Butterworth, Sophie; Rivers, Clare; Fullarton, Marnie; Murphy, Colm; Beale, Victoria; Neil-Dwyer, Jason; Van Eeden, Simon; Van Eeden, Stephanie; Hodgkinson, Peter D.; Smyth, Alistair; Sainsbury, David C
Background: There may be many reasons for delays to primary cleft surgery. Our aim was to investigate the age of children undergoing primary cleft lip or primary cleft palate repair in 5 cleft centers within the United Kingdom. Identify the reasons for delayed primary cleft lip repair (beyond 6 months) and delayed primary palate repair (beyond 13 months). Identify children who had a cleft lip and/or palate (CL±P) that was intentionally unrepaired and the reasons for this. Methods: A retrospective, multicenter review of patients born with a CL±P between December 1, 2012, and December 31, 2016. Three regional cleft centers, comprising of 5 cleft administrative units in the United Kingdom participated. Results: In all, 1826 patients with CL±P were identified. Of them, 120 patients had delayed lip repair, outside the expected standard of 183 days. And, 178 patients in total had delayed palate repair, outside the expected standard of 396 days. Twenty (1%) patients had an unrepaired cleft palate. Conclusions: This large retrospective review highlights variations between centers regarding the timing of lip and palate surgery and details the reasons stated for delayed primary surgery. A small number of patients with an unrepaired cleft palate were identified. All had complex medical problems or comorbidities listed as a reason for the decision not to operate and 50% had a syndromic diagnosis. The number of patients receiving delayed surgery due to comorbidities, being underweight or prematurity, highlights the importance of the cleft specialist nurse and pediatrician within the cleft multidisciplinary team.